Green Shipping Development: Carbon Emission Reduction Strategies in the Shipping Industry - Kyaw, Aung Ye; Syaifullah, Syaifullah (Maritime Park: Journal of Maritime Technology and Society, 2025)
This study examines the development of green shipping strategies to reduce carbon emissions in the shipping industry. Using a mixed-method approach, the study was conducted by analyzing data from 50 sample ships and involving 150 maritime industry stakeholders. The results showed that the implementation of green shipping technology can reduce carbon emissions by up to 23.5%, with a combination of technologies achieving a reduction of up to 35%. Economic analysis revealed an average payback period of 3.2 years. The study resulted in a three-pillar strategy recommendation that includes gradual investment in environmentally friendly technologies, crew capacity development, and industry collaboration for infrastructure development. These findings provide significant contributions to the development of effective and sustainable carbon emission reduction strategies in the shipping industry.